A case study on risk-based maintenance of wind turbine blades with structural health monitoring. Issue 3 (6th February 2021) - Nielsen, Jannie S.; Tcherniak, Dmitri; Ulriksen, Martin D.
Abstract: The paper presents a case study demonstrating the methods used to estimate the value of the information (VoI) delivered by a structural health monitoring (SHM) system. The monitored object is a blade of an operating wind turbine. The case study shows how the maintenance cost optimization can be performed using a risk-based approach cast in a Bayesian decision analysis framework, in which probabilistic models are developed for blade deterioration processes, blade inspections, and SHM systems. The paper also provides a parameter study, which demonstrates how the potential benefit of SHM highly depends on the reliability of the utilised SHM system and how the SHM observations are used for decision making on the inspections and maintenance.